Studies on teaching and learning foreign languages in Mexico (2012–2021) (Revista Investigium IRE Ciencias Sociales y Humanas, 2023)
This article describes and reflects on research related to the teaching and learning of foreign languages in Mexico published in indexed journals between 2012 and 2021. The paper is organized into four sections: the first provides an overview of the context in which research in this field is being carried out in Mexico, while the second presents the conceptual approach and methodology used. The third section describes the central results related to the publications reviewed, and the fourth section closes with some conclusions and final reflections.